Stosunek św. Ambrożego do małżeństwa i życia rodzinnego - Naumowicz, Józef (Vox Patrum, 1985)
It would be a methodological failure, on the basis of St. Ambrose’s works, which aim at encouraging and defending the dignity of virgins’ or widows’ state, to conclude on the author’s negative attitude to matrimony and family life.